Effect of turbulent dispersion on hydrodynamic characteristics in a liquid jet ejector. (1st December 2018) - Sharma, Deepankar; Patwardhan, Ashwin; Ranade, Vivek
Abstract: Gas induction using a liquid jet is an extensively studied phenomenon. Many studies have been published detailing various hydrodynamic and mass transport aspects of gas induction in ejectors. Conversely, multiple studies have been published detailing jet dynamics, jet break up, nozzle geometry, effects of turbulence etc. In the modelling of the jet ejector systems CFD framework is used as the flow of gas is coupled with the liquid flow and the flow parameters like volume fraction, pressure drop/profile and velocity profiles both local and average are highly interdependent. Hence, it becomes important to capture all the flow physics in the simulations in order to understand the hydrodynamics. In the previous models the effect of turbulent dispersion was not included which led to incorrect calculation of phase profile, and other related parametric values. In the present work, the turbulence effects and its impact on the jet dynamics and gas induction rate in an ejector have been studied. Capturing the correct phase as well as velocity profile is imperative for the extension of the model to mass transfer and reactions. Lastly, other hydrodynamic properties like pressure drop, phase hold up and pressure profile help better the design correlations for jet ejectors. Highlights: The jet break up and dispersion is caused by turbulence. The implementation of turbulent drift force in a Euler-Euler framework correctly predicts the phase dispersion in an ejector. The bubble diameter and the gas induction correlation is not very strong. Turbulent Schmidt number shares an inverse relationship with the dispersion of the jet.